THE PRE-HISPANIC CULTURAL INTERACTION OF ANDEAN VALLEYS, SUB-ANDEAN AND AMAZONIAN REGIONS, NORTH OF ECUADOR - Arellano, Jorge (2013)
This article shows the importance of the environmental events for the pre-Hispanic cultures of the InterAndean basins of Ecuador to choose the right paths to make contact with Sub-Andean and Amazonian cultures. Here, we analyze archaeological data recorded in one of the paths used by the Quito-Guayllabamba valley cultures to the Sub-Andean hills and Amazonian foothills. This route was controlled by the ceramic Phase Cosanga, historically known as Quijos. Archaeological evidence suggests that this culture may have been the intermediary for contacts with the lower Amazon. Meanwhile archaeological data related to the Amazonian ceramic Tradition corrugated-falsocorrugated shows that this tradition tried to expand into the Sub-Andean hills following the Quijos River valley. The expansion of both cultures may have been stop by the constant environmental events product of the volcanic activity of El Reventador.